Partai Politik Dalam Perspektif Pertanggungjawaban Pidana Korupsi - Wangga, Maria Silvya Elisabeth (Law, Development and Justice Review, 2023)
Political parties fulfill the criteria as corporations in the Corruption Crime Eradication Law. Political parties that benefit from the results of criminal acts of corruption have not been held criminally responsible for their administrators or members. This paper examines the rationale for criminal accountability of political parties in criminal acts of corruption committed carried out by the management or members and their criminal law policies. This paper is a type of normative juridical research in a broad sense. The basic idea of criminal accountability for political parties in acts of corruption must consider six things, among others; blameworthiness, need, moderation, inefficiency, control costs, and the victim's interests. For future reforms, it is necessary to regulate the formulation of the main types of punishment that are structural or institutional in nature.